Surface heat transfer study of ultra heavy plate during quenching process of jet array impingement. (5th May 2017) - Fu, Tian-liang; Wang, Zhao-dong; Deng, Xiang-tao; Han, Jun; Wang, Guo-dong
Highlights: Ultra heavy plates with large fractured surface are important structural materials. Multi-channel temperature tracking recorder are developed. Useful for temperature field computation and regulation of texture performance. Abstract: Heat treatment is a key technology to improve the performance of ultra heavy plates with large fractured surface. Roller-type jet quenching test facility and multi-channel temperature tracking recorder dedicated for ultra heavy plate are developed in present work to measure the temperature drop curves of the plate with a thickness of 84 mm during quenching process when jet velocity, Re and water flow density are 3.39–26.8 m/s, 12, 808–117, 340 and 978.7–6751.5 L/(m 2 min), respectively. Effect of multi-beam round hole jet array on heat transfer of ultra heavy plate are analyzed. The results indicate that parameters such as jet velocity, water density affect the heat transfer mechanism of jet stagnation zone and parallel flow zone of plate surface, which further exerts influence on the maximum heat flux of different positions away from stagnation points. Mixed heat transfer and "heat flux shoulder" phenomena can be observed in surface parallel flow zone when jet velocity is relatively lower (3.39 m/s); film boiling heat transfer mechanism disappears with increasing jet velocity (11.16 → 26.8 m/s) and maximum heat flux moves towards superheat positions at lower surface. Relevant study would be beneficial for the temperature field computation and regulation of texture performance of ultra heavy plate during quenching process.